The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.iecr.3c01448
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Smart Wettability-Regulating Surface for Enhancing Pool Boiling Heat Transfer Using the Lattice Boltzmann Method

Yanwei Hu,
Chunwei Wang,
Yurong He

Abstract: The wettability of a heating surface has a significant effect on boiling heat transfer (BHT). However, the requirements of the boiling process for surface wettability under different superheat levels change dynamically, and static wettability cannot meet this dynamic demand. Hence, based on the Rohsenow correlation and Kandlikar correlation, the best corresponding relationship between temperature and wettability was found, and a smart wettability-regulating surface with wettability varying with superheat was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The overall model was 99.3% accurate and could predict moisture more accurately than a single measurement, as well as obtaining 3-D dynamic information on gas–solid two-phase flow. Hu et al investigated the effect of wettability of a heated surface during boiling heat transfer and designed a smart wettability-regulating surface whose wettability varies with superheat. The results indicated that critical heat flux of the smart surface was identical to that of the hydrophilic surface and 19.8% higher than that of the hydrophobic surface.…”
mentioning
confidence: 99%
“…The overall model was 99.3% accurate and could predict moisture more accurately than a single measurement, as well as obtaining 3-D dynamic information on gas–solid two-phase flow. Hu et al investigated the effect of wettability of a heated surface during boiling heat transfer and designed a smart wettability-regulating surface whose wettability varies with superheat. The results indicated that critical heat flux of the smart surface was identical to that of the hydrophilic surface and 19.8% higher than that of the hydrophobic surface.…”
mentioning
confidence: 99%